Козлова Т. О. Іконічність у лексиці індоєвропейської прамови - Приходько, А. (Мовознавство, 2016)
Рецензія на книгу: Козлова Т. О. Іконічність у лексиці індоєвропейської прамови. Запоріжжя : Кругозір, 2015.— 640 с.